Optimising the structure of a cascaded modular battery system for enhancing the performance of battery packs - Fares, Ahmed; Klumpner, Christian; Sumner, M. (2018)
The overall performance of battery packs may be affected by imbalances between the series connected cells which is more likely in packs with high number of cells needed to provide a high voltage as needed for example in electric vehicles. In this case, the overall capacity and power capability of the pack is limited by the weakest cell in the stack which results in incomplete utilization of the pack’s capabilities. In traditional centralized battery systems (TCBS), this is addressed by implementing cell active/passive balancing circuitry/techniques which restore some of the pack’s energy capability. This paper proposes the use of cascaded modular battery systems (CMBS) to remove the need for extra balancing circuitry and maximises the performance and reliability of a battery system containing unequal matched/aged cells. The analysis is assessing the CMBS overall system efficiency, reliability and weight compared to the TCBS for a design of a 300V/3.6kW battery system as a case study.